Coral reefs eco tourism sustainability management In the Gili Labak Island using rapfish method - Firman Farid Muhsoni; Mahfud Efendy (Jurnal Kelautan, 2017)
The purpose of this research is to give direction of management of Gili Labak Island by considering multidimensional factors. The method used is Rapfish. This method uses the ecological, resource, economic, social, legal and institutional dimensions. Rapfish Gili Labak's analysis results for the ecological dimension show a value of 62.3 in a fairly sustainable category. The resource dimension shows a value of 63.07 in fairly sustainable categories. The economic dimension shows the value of 10.15 in the unsustainable category. the social dimension of value of 17.8 in the unsustainable category. Legal dimensions and institutional values of 5.36 in non-sustainable categories. Multidimensional analysis results show sustainability index in less sustainable category (value 34,24). After interference is increased it becomes quite continuous (value 74.99). This interference is described in the recommendations. Recommendations are made on the lesser dimensions, namely the legal and institutional fields, the economic field and the social field.